Process optimization by response surface methodology and kinetic modeling for synthesis of methyl oleate biodiesel over H3PW12O40 anchored montmorillonite K10 - Nandiwale, Kakasaheb Y.; Bokade, Vijay V. (Industrial & Engineering Chemistry Research, 2014)
Heterogeneous acid catalysts comprised of 1030% (w/w) H3PW12O40 anchored to montmorillonite (K10) were used for synthesis of methyl oleate biodiesel by esterification of free fatty acid (oleic acid) with methanol in closed batch system. Response surface methodology (RSM) was employed to optimize esterification of oleic acid with methanol over 20% (w/w) H3PW12O40/K-10. The effects of various process parameters such as catalyst loading, molar ratio, and reaction temperature on oleic acid conversion were addressed by BoxBehnken experimental design (BBD). Coefficient of determination (R-2) of this model was 0.996. 20% (w/w) H3PW12O40/K-10 was proved to be potential catalyst with 100% oleic acid conversion at optimized process parameters and with reusability of four cycles. Moreover, a second-order pseudohomogeneous (PH) kinetic model has been proposed and validated (R-2 > 0.97) with experimental data. Kinetics confirmed that esterification reaction is performed in the kinetic regime due to high activation energy of 43.7 kJ mol(-1).